Analysis of Paylater Usage on Impulsive Buying Behavior - Hamidah, Syifa Fauziah; Pratama, Roro Arinda Reswanti Julian; Permana, Rezi Muhamad Taufik (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2024)
The use of new financial technologies, such as PayLater services, has grown rapidly in recent years. This service allows consumers to buy goods without paying directly at the time of purchase, but instead pay later within a certain period of time. Although this service provides convenience and flexibility in shopping, unwise use can increase the risk of impulsive purchasing behavior. The purpose of this study is to find out how to analyze the relationship between PayLater use and impulsive shopping behavior. The analytical method used is a quantitative method with descriptive analysis. To process the data, the author used Microsoft Excel 2019 and SPSS 26 For Windows. The survey method was carried out by distributing questionnaires to respondents who used PayLater services and measuring the level of their impulsive behavior in buying goods online. The study results show a strong relationship between impulsive buying behavior and pay-later users.